Five ways to get a grip on embedding Equity, Diversity, Inclusion and Accessibility into survey design for non-equity related health professions education research topics - Lekuti, Mujeedat; Laios, Eleftheria; Chung, Wiley (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2026)
Health professions education research must integrate Equity, Diversity, Inclusion, and Accessibility (EDIA) principles to ensure meaningful and impactful initiatives. Embedding these principles into research methods from the outset helps maintain the integrity of the research and ensures its outcomes align with EDIA values. Recognizing the limited guidance on incorporating EDIA principles into non-equity-related HPE survey methodology, we developed guidelines to address this gap. This led to the creation of ‘Five Ways to Get a Grip on Embedding EDIA into Survey Design for non-equity related Health Professions Education Research,’ which includes guidelines for integrating (1) diverse sources of knowledge, (2) usability, (3) context sensitivity, (4) bidirectionality, and (5) accessibility. Applying these guidelines can help make surveys inclusive and respondent-centered, providing a strong foundation for enhancing survey design and embedding EDIA principles within health professions education research.